HUBUNGAN SEBELUM DAN SESUDAH PENYULUHAN DENGAN PENCEGAHAN CORONA VIRUS DESEASE-19 PADA PELAJAR ATLET DI UPT KEBAKATAN OLAHRAGA PPLP-DISPORA PROVINSI SUMATERA UTARA TAHUN 2022 - Ari chistina s2 (Jurnal Kajian Kesehatan Masyarakat, 2023)
Corona virus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV- is a virus that attacks the respiratory system. Indonesia is in 20th place from the country with the highest COVID-19 cases in the world. Indonesia is the country with the highest number of COVID-19 cases in the world Southeast Asia. Data from the UPT for Sports Talent, Student Training Education Center, Youth Sports Service (PPLP-DISPORA) of the North Sumatra Provincial Government, on July 16, 2021, there were 4 athletes who were positive for Covid-19 through a rapid antigen test and isolation for 14 days. The study aims to knowing the relationship before and after counseling with the prevention of Corona Virus Disease-19 in student athletes at UPT Sport Kebakatan PPLP-DISPORA North Sumatra Province in 2022. The study used an experimental method, the experiment in question was a pre-experimental design using (one group pretest and post test). The population is student athletes as many as 151 people at UPT Sport Talent P PLP-DISPORA North Sumatra Provincial Government. The sample using the Slovin formula is 60 student athletes. The sampling technique is systematic random sampling. Data analysis was carried out by univariate analysis, bivariate analysis with Chi square. The results showed that before counseling on the prevention of Corona Virus Disease-19 the less category was 40 people (66.7%) and good 20 people (33.3%) and after counseling on the prevention of Corona Virus Disease-19 the less category was 4 people (6 ,7%) and both 56 people (93.3%). The conclusion is that there is a relationship before and after counseling with the prevention of Corona Virus Disease-19 in student athletes at UPT Sport Talent PPLP-DISPORA North Sumatra Province in 2022 with the results of the Chi square p=0,000 < p=0,05. It is recommended that there is a need for policies from the North Sumatra Province Education and Sports Office to emphasize the implementation of Covid-19 prevention. After there is a policy from the North Sumatra Province Education and Sports Office, it is necessary to monitor and supervise the implementation of the COVID-19 prevention policy